2003
DOI: 10.1212/01.wnl.0000083988.98336.a3
|View full text |Cite
|
Sign up to set email alerts
|

Headache associated with sexual activity

Abstract: Mean age at onset, a male preponderance, a predominantly bilateral and occipital pain, and a high comorbidity with other primary headaches are in concordance with case reports in the literature. The authors found two peaks for the age at onset, however. There was no clinical evidence proving subtypes 1 and 2 to be distinct disorders. HSA types 1 and 2 may be different manifestations of the same disease rather than distinct entities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
145
2
28

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(186 citation statements)
references
References 25 publications
8
145
2
28
Order By: Relevance
“…The patients were similar to other cohorts of patients with PHSA [8] with respect to sex ratio (M:F=19:6; 76% male), age range (19-56 years), mean (±SEM) age (41.6±8.8 years) and PHSA subtype (preorgasmic:orgasmic=7:18). All patients were offered non-invasive angiography to exclude underlying aneurysm.…”
Section: Resultssupporting
confidence: 81%
“…The patients were similar to other cohorts of patients with PHSA [8] with respect to sex ratio (M:F=19:6; 76% male), age range (19-56 years), mean (±SEM) age (41.6±8.8 years) and PHSA subtype (preorgasmic:orgasmic=7:18). All patients were offered non-invasive angiography to exclude underlying aneurysm.…”
Section: Resultssupporting
confidence: 81%
“…The frequency of HSA was 0.28% in 1 health checkup study [14] whereas 6.06% in 1 emergency service-based study of any sexual complication events [15], and ranged from 0.28% to 1.63% (average being 0.36%) in 5 clinic-based studies [16] Table 2). Frese et al [26] suggested the frequency of HSA to be 1% in their database but the total number of headache patients was unknown.…”
Section: Resultsmentioning
confidence: 99%
“…In the series of Frese et al [26], HSA occurred under specific act of intercourse in 5 (8.4%) out of 51 patients, including kneeling position in 2, supine position in 2, and fellatio in 1 patient respectively. In the series of Valença et al [24], a 44-year-old woman suffered HSA under masturbation or intercourse with her husband in standing position.…”
Section: Sexual Positionmentioning
confidence: 91%
See 1 more Smart Citation
“…Pre-orgasmic headache may be related tospace-occupyinglesions.Orgasmicheadacheisoftensevereand excruciating, whether due to aneurysm rupture or to the explosive component of benign coital headache. Post-orgasmic headache mayoccurasamanifestationofmigraine (Banerjee,1996).Astudy by Frese et al (2003) stratified headaches associated with sexual activity and found that there was a male preponderance. It has two onset peaks (between 20-24 and 35-44 years).…”
mentioning
confidence: 99%